Visible Light Activation of Boronic Esters Enables Efficient Photoredox C(sp2)–C(sp3) Cross‐Couplings in Flow. Issue 45 (6th October 2016) - Lima, Fabio; Kabeshov, Mikhail A.; Tran, Duc N.; Battilocchio, Claudio; Sedelmeier, Joerg; Sedelmeier, Gottfried; Schenkel, Berthold; Ley, Steven V.
Abstract: We report herein a new method for the photoredox activation of boronic esters. Using these reagents, an efficient and high‐throughput continuous flow process was developed to perform a dual iridium‐ and nickel‐catalyzed C(sp 2 )–C(sp 3 ) coupling by circumventing solubility issues associated with potassium trifluoroborate salts. Formation of an adduct with a pyridine‐derived Lewis base was found to be essential for the photoredox activation of the boronic esters. Based on these results we were able to develop a further simplified visible light mediated C(sp 2 )–C(sp 3 ) coupling method using boronic esters and cyano heteroarenes under flow conditions. Abstract : Solubility rules ! A high‐throughput flow process was developed to perform a dual Ir/Ni‐catalyzed photoredox C(sp 2 )–C(sp 3 ) coupling of boronic esters by circumventing solubility issues associated with potassium trifluoroborate salts. Formation of a Lewis acid–base adduct with a pyridine‐derived Lewis base was found to be essential for the photoredox activation of the boronic esters (see scheme).